SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN HAMA TERPADU PADA TANAMAN PADI BE RPBEANSGIESNDALIAN TEKNOLOGI INFORMASI / Information Tecnology Based Decision Support System for Integrated Pest Management on Rice - Widiarta, I Nyoman (Badan Penelitian dan Pengembangan Pertanian, 2021)
Pest and disease are important biotic obstacles to increase rice yield and production in Indonesia since adoption of green revolution to increase rice yield. This is partly due to the irrational use of pesticides. This paper is a review on information technology (IT) based decision support system (DSSs) in line to the integrated pest management (IPM) implementation strategy for extensionists and farmers in the fields. IPM integrates compatible control techniques to manage pest populations below the economic injury level. IT based DSSs ultimately needed so that extension workers and farmers can quickly access sources of information about pests and diseases as well as prediction of development and control techniques to implement IPM. Web based DSSs to grow healthy rice plant, pest observation and monitoring, cyber extension to make famers an expert on IPM were available, except on how to identify and utilize natural enemies are still lacking. Indonesia need to develop more IT based DSSs which accessible on web as well as on smartphone and create enabling environment for improving IPM implementation on rice not only by officer but also gradually by farmers it self to control pests and diseases of rice which are still an obstacle in increasing production.Keywords: Rice, pest, diseases, integrated pest management, information technologyÂ AbstrakSejak inovasi revolusi hijau diintroduksikan di Indonesia, hama dan penyakit tanaman semakin berkembang sehingga menghambat upaya peningkatan produktivitas dan produksi padi. Hal ini antara lain disebabkan oleh penggunaan pestisida yang tidak rasional. Tulisan ini mengulas kesiapan sistem pendukung pengambilan keputusan (SPPK) berbasis teknologi informasi (TI) dalam pengendalian hama terpadu (PHT) oleh penyuluh maupun petani di lapangan. PHT mengintegrasikan berbagai teknik pengendalian hama dan penyakit agar tetap berada di bawah ambang ekonomi. TI diperlukan agar penyuluh dan petani dapat dengan cepat mengakses sumber informasi tentang jenis hama dan penyakit tanaman serta perkiraan perkembangan dan teknik pengendalian untuk penerapan PHT. SPPK berbasis TI yang bertujuan menjadikan tanaman tumbuh sehat, pengamatan dan monitoring perkembangan hama dan penyakit, serta penyuluhan berbasis web sudah tersedia, kecuali identifikasi dan cara pemanfaatan musuh alami. Oleh karena itu perlu dikembangkan SPPK berbasis TI yang dapat diakses melalui web maupun telepon pintar dan menciptakan lingkungan yang memungkinkan untuk meningkatkan implementasi PHT tidak hanya oleh petugas tetapi juga petani secara bertahap dalam upaya mengendalikan hama dan penyakit padi yang masih menjadi kendala dalam peningkatan produksi.Kata kunci: Padi, hama, penyakit, pengendalian hama terpadu, teknologi informasi